2022
DOI: 10.1021/acsami.2c09122
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Reusable Carbon Dot/Gold Nanoparticle/Metal–Organic Framework Film for Fluorescence Detection of Lead Ions in Water

Abstract: Solid-state sensing platforms are desirable for the development of reusable sensors to promote public health measures such as testing for drinking water contamination. A bioinspired metal–organic framework (MOF)-based material has been developed by imitating metal–protein interactions in biological systems to attain high sensitivity and selectivity to Pb2+ through fluorescence sensing. A zirconium terephthalate-type framework (also known as NH2-UiO-66) was modified with both gold nanoparticles and thiol-functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…15a). 192 The surface plasmon resonance of the metal NPs combines with the fluorescence signal where the film of its powder shows a significant change in fluorescence intensity, which is used to selectively detect the Pb( ii ) ions as shown in Fig. 15b.…”
Section: Applicationsmentioning
confidence: 99%
“…15a). 192 The surface plasmon resonance of the metal NPs combines with the fluorescence signal where the film of its powder shows a significant change in fluorescence intensity, which is used to selectively detect the Pb( ii ) ions as shown in Fig. 15b.…”
Section: Applicationsmentioning
confidence: 99%
“…Cara M. Doherty et al reported the HS-C/Au(x)/UiO-66 composite film as a solid-state sensor for Pb 2 + detection. [88] Pb 2 + could cause fluorescence quenching of the sensor HS-C/Au(x)/UiO-66 due to the energy Figure 6. The synthetic route of the CDs, CDs@Eu-MOFs and detection mechanism for Hg 2 + .…”
Section: Metal-organic Framework (Mofs)mentioning
confidence: 99%
“…Globally, water contamination and its treatment have emerged as a growing concern. In recent decades, remarkable efforts have been made to overcome the challenges of wastewater treatment, as the water pollution level has risen due to an influx of pathogenic microorganisms and toxic pollutants entering the regular water cycle in aquatic environments, which has dire implications for both terrestrial aquatic and ecosystems. It is well documented in the literature that wastewater sources are one of the largest conceivable water resources, and their reuse is expected to offset the need for more clean water . In light of these facts, a number of technologies such as sedimentation, coagulation, filtration, adsorption, and membrane technologies have been developed for wastewater treatment; however, they have high operating costs and can introduce dangerous secondary contaminants into the biological system. , …”
Section: Introductionmentioning
confidence: 99%